THE ROLE OF TONGUE TWISTERS IN THE PROCESS OF TEACHING PHONETICS (Academicia Globe: Inderscience Research, 2023)
The article is devoted to show all modern methods of teaching English with tongue twisters that are frequently used by English teachers in practical courses. The aim of the study is to investigate what problems the students faced while acquiring good pronunciation and speaking skills and how tongue twisters assisted.